Investigation and Calculation of Magnetic Field in Tubular Linear Reluctance Motor Using FEM - MOSALLANEJAD, A.; SHOULAIE, A. (Advances in Electrical and Computer Engineering, 2010)
In this paper the magnetic flux density of tubular linear reluctance motor (TLRM) in open type magnetic circuit is studied. Also, all magnetic flux density calculation methods in winding of tubular linear reluctance motor are described. The effect of structure parameters on magnetic flux density is also discussed. Electromagnetic finite-element analysis is used for simulation of magnetic field, and simulation results of the magnetic field analysis with DC voltage excitation are compared with results obtained from calculation methods. The comparison yields a good agreement.